2022
DOI: 10.3390/children9020185
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Opportunities for Patient-Reported Outcome Implementation: A National Pediatrician Survey in the United States

Abstract: Purpose: To characterize pediatricians’ perceived barriers and areas of confidence in assessing patient-reported outcomes (PROs) in the U.S., and to test associations of these factors with implementing PRO assessment. Methods: Using a random sample from the members of American Medical Association, we recruited general pediatricians and pediatric subspecialists to complete a survey (July 2011 to December 2013). Perceived barriers and confidence in PRO assessment were compared by age, pediatric specialty (genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…Integration of PROMs in real-world clinical practice is still limited due to a multifactorial set of hindering factors [ 28 ]. Since HRQoL tools constitute the most frequently used generic PROMs, a number of factors burden their application.…”
Section: Discussionmentioning
confidence: 99%
“…Integration of PROMs in real-world clinical practice is still limited due to a multifactorial set of hindering factors [ 28 ]. Since HRQoL tools constitute the most frequently used generic PROMs, a number of factors burden their application.…”
Section: Discussionmentioning
confidence: 99%
“…Different barriers to the use of Patient-Reported Outcome Measures (PROMs) in clinical care with the paediatric population have been identified in the literature [25]. In this case, the ICIQ-CLUTS questionnaire is feasible because it takes little time for children or parents to complete it (less than 4 min), and it is simple to score, reasons that facilitate its use in clinical daily routine.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous review studies have identified the measurement properties of extant PRO measures [ 22 , 25 ], and other reviews have identified uncertainty about the clinical validity of PRO measures as an implementation barrier [ 18 , 19 ]. To bridge these review topics, we have identified often unreported measurement properties that could provide evidence about the clinical utility of the PRO measures including clinical anchors, clinically meaningful cutpoints and MIDs, responsiveness, predictive validity, response-shift effects, and cross-cultural validity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinicians report the lack of clinically meaningful cutpoints and MIDs as another application barrier [ 18 , 19 ]. Only four of the extant generic PRO measures included in our review established cutpoints and/or MIDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation